S-CDK-regulated bipartite interaction of Mcm10 with MCM is essential for DNA replication - Wang, Xueting; Liu, Lu; Chen, Mengke; Quan, Yun; Zhang, Jiaxin; Lou, Huiqiang; Xia, Yisui; Chen, Hongxiang; Hou, Wenya (Frontiers in Cell and Developmental Biology, 2024)
Mcm10 plays an essential role in the activation of replicative helicase CMG through the cell cycle-regulated interaction with the prototype MCM double hexamer in Saccharomyces cerevisiae. In this study, we reported that Mcm10 is phosphorylated by S-phase cyclin-dependent kinases (S-CDKs) at S66, which enhances Mcm10–-MCM association during the S phase. S66A single mutation or even deletion of whole N-terminus (a.a. 1–128) only causes mild growth defects. Nevertheless, S66 becomes indispensable in the absence of the Mcm10 C-terminus ((a.a. 463–571), the major MCM-binding domain. Using a two-degron strategy to efficiently deplete Mcm10, we show that mcm10-S66AΔC has a severe defect in proceeding into the S phase. Notably, both lethality and S-phase deficiency can be rescued by artificially tethering mcm10-S66AΔC to MCM. These findings illustrate how the Mcm10–MCM association is regulated as a crucial event in DNA replication initiation.